The Role of Computed Tomography in the Localization of Adrenal Cortex Tumors - Baranowska, B.; Misiorowski, W.; Pacho, R.; Wysocki, M.; Kobuszewska, M.; Zgliczyński, S. (Nuklearmedizin - NuclearMedicine, 1982)
The aim of this study was to evaluate the usefulness of computed tomography in the localisation of adrenal tumors producing aldosterone and Cortisol. One case each of Conn’s and Cushing’s syndrome are described. The diagnosis of Conn’s syndrome was established by demonstrating an elevated plasma aldosterone level “at rest” and its decrease after stimulation, the absence of plasma renin activity and a lowered plasma potassium level. The diagnosis of Cushing’s syndrome due to adrenal adenoma was established by demonstrating the typical clinical features, an abnormal diurnal rhythm of Cortisol and ACTH secretion and an increased urine excretion of 17-OHCS without suppression by large doses of dexamethasone. The localisation and the size of the tumors as determined by computed tomography were confirmed during surgery.